Anticancer Effects of Combined γ-Tocotrienol and PPARγ-Antagonist Treatment are Associated with a Suppression in Adipogenic Factor Expression - Abhita Malaviya,; Parash Parajuli ,; Paul W. Sylvester, (Journal of Pharmacy and Nutrition Sciences, 2014)
Cancer cells reprogram their metabolism to meet the demands of accelerated growth. Glucose is the primary source of energy for cancer cells, but under conditions of high-energy demand lipids and free fatty acids become increasingly important. PPARγ is a member of the nuclear receptor superfamily and acts to regulate adipocyte differentiation and lipid metabolism. However, in many types of cancer, PPARγ activity is elevated in order to increase production of adipogenic factors [1, 2]. γ-Tocotrienol is an isoform of vitamin E that displays potent anticancer activity [3]. Previous studies have shown that the antiproliferative effects of combined treatment of ã-tocotrienol with PPAR?antagonists was associated with a reduction in PPARγ activity, expression of PPAR? and RXR, and suppression in Akt activation in MCF-7 and MBA-MB-231 human breast cancer cells [4]. The present study was conducted to determine the effects of combination treatment with these agents on adipogenic factor levels in rapidly proliferating human breast cancer cells. Western blot and qRT-PCR studies showed that combined treatment of ?-tocotrienol with PPAR?antagonists not only suppressed the adipogenic proteins, C/EBPγ and SREBP-1c, but also decreased their target lipogenic enzymes, ap2, FAS, and HMGCoR. However, treatment effects were also observed in PPARγ silenced breast cancer cells, indicating that these effects are mediated through PPARγ-independent mechanism. These findings suggest the combined treatment of γ-tocotrienol with PPARγ antagonist may have potential as a therapeutic strategy in the treatment of breast cancer.